USER-CENTERED DESIGN SEBAGAI METODE PENINGKATAN KONTROL KOGNITIF PADA LINI ASSEMBLY (STUDI KASUS PT. KUBOTA INDONESIA) - Susanto, Novie (TEKNIK, 2011)
In developing countries like Indonesia, the rationalization of production processes and systems will increase.Challenge that emerged significantly is the increase in planning efficiency. A prospective approach to reduce theplanning effort is the development of a production system capable of optimizing itself during the process. On theassembly line PT. Kubota Indonesia found that the workers perform assembly process with a sequence that is notplanned as a result of the lack of a standardized sequence of process companies and lead to cognitive controlthat are not stable and continuous learning process. Because this issue contrary to the concept of efficiency inplanning, it takes an automated system with a complete and fully optimized (self-optimizing production system).The purpose of this study is to apply the planning efficiency through implementation of optimized productionsystem (self-optimizing production systems) in assembly-line PT. Kubota Indonesia. Data obtaining done by thedetermination of primary and secondary variables include the perception of cognitive control, a solution basedon the memory (memory), and action. Repairs are carried out is by applying self-optimizing production systemconsisting of 4 steps: the development of cognitive architecture is to determine the sequence of work andapplying it to extend the software, implementation of individual modules is through the use of hand screw, thedevelopment of human machine interfaces in hand tool screw is through the explanation task analysis andimplementation and evaluation of improvement is the use of robotic assembly in the assembly processenvironment.